Novel three-sinus enlargement technique for supravalvular aortic stenosis without aortic transection. Issue 1 (December 2016) - Yokoyama, Shinya; Nagato, Hisao; Yoshida, Yuichi; Nagasaka, Shigeo; Kaneda, Kozo; Nishiwaki, Noboru
Abstract Background Although repair of a supravalvular aortic stenosis (SVAS) can be performed with low mortality rates, surgery for the complex form of SVAS continues to be associated with a high incidence of residual stenosis. Case presentation The patient was referred to our hospital at 1 month of age and was diagnosed with aortic valve stenosis (AS) by using echocardiography. Cardiac catheterization revealed moderate AS, and subsequent left ventriculography revealed discrete stenosis of the sino-tubular junction and a narrowed proximal ascending aorta. We performed a reconstructive operation for such heart defects involving novel three-sinus and ascending aorta enlargement without aortic root transection in a 6-month-old boy. Conclusion Our novel three-sinus enlargement technique is suitable for treating each type of SVAS and is a useful method for a baby particularly less than 10 kg without disturbing the growth of the ascending aorta.